Potensi Desa Giricahyo, Gunung Kidul dengan Pengenalan Budidaya Jahe Merah dan Pembelajaran TOGA (Tanaman Obat Keluarga) - Nernere, Maria (Jurnal Atma Inovasia, 2023)
Gunung Kidul is one of the district that was located in Daerah Istimewa Yogyakarta. Gunung kidul is located on mountains that has a specific characteristics of land. Which is a less fertile compared to others due to the lime contents. This kind of land is perfect for our project, red ginger. It doesn’t need to be watered much, and easy to cultivate. The other thing is how red ginger is also considered as one of family medicine group called as TOGA in Bahasa. Therefore, besides talking about red ginger, we also give information about several other plants that is considered as TOGA that is beneficial for health. Literature study method and secondary data were used in order to compile our findings. Through the outputs we created, we hope that these outputs will help the people around Gunung Kidul in creating a new living that suits the district’s condition.